Adapatation of Digital Marketing Activation After the COVID-19 Pandemic at Anantara Seminyak Bali Resort - Hilda Kosasih; Gabriela Felicita Putri Kurniadi; Flavia Maharani Yunazar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to analyze the digital marketing activation in the hotel industry in Bali as their adaptation to consumer behavior post-COVID-19 pandemic. This study was conducted by qualitative descriptive with a study case approach to know the digital marketing adaptation applied by Anantara Seminyak Bali Resort in dealing with digital consumers. Through this study, the researchers found that Anantara Seminyak Bali Resort has adapted digital marketing to the stages of digital consumer behavior after the COVID-19 pandemic.